TANGGAPAN WISATAWAN TERHADAP KULINER TRADISIONAL DI DESA WISATA BOKOR KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI - Wibowo, Arie; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research purposed to get know about how tourist response to the traditional culinary the tourist villagge Bokor sub-distric west rangsang regency archipelago meranti, Riau ProvinceThis research used qualitative desciptive method to analyze the problems. The sample in this research are 50 samples by using accidental sampling. And then the technique to collected data in this research are using questionnaire, interview, and observation. And it was using likert scale to know the length of intervals.Based on the research results, the tourist response about traditional culinaryin bokor village rangsang barat sub-district kepulauan meranti regency was in four step, there were looking the preparation, how to make, presenting and have the food.Keywords : tourist response, traditional culinary, the tourist villagge Bokor